Circular RNA MYLK as a competing endogenous RNA promotes bladder cancer progression through modulating VEGFA/VEGFR2 signaling pathway. (10th September 2017) - Zhong, Zhenyu; Huang, Mengge; Lv, Mengxin; He, Yunfeng; Duan, Changzhu; Zhang, Luyu; Chen, Junxia
Abstract: Accumulating evidences indicate that circular RNAs (circRNAs) play a vital role in modulating gene expression. However, the mechanisms underlying circRNAs remain largely elusive. Here, we screened circRNA and mRNA expression profiles of bladder carcinoma (BC) using microarray analysis. We found that circRNA-MYLK and VEGFA were significantly up-regulated and co-expressed in BC. Importantly, circRNA-MYLK levels were related to the progression of stage and grade of BC. Mechanistically, we demonstrated that circRNA-MYLK could directly bind to miR-29a and relieve suppression for target VEGFA, which activated VEGFA/VEGFR2 signaling pathway. Functionally, we found that ectopically expressing circRNA-MYLK accelerated cell proliferation, migration, tube formation of HUVEC and rearranged cytoskeleton. Moreover, up-regulating circRNA-MYLK promoted epithelial-mesenchymal transition (EMT). Whereas circRNA-MYLK knockdown decreased cell proliferation, motility, and induced apoptosis. Finally, up-regulating circRNA-MYLK promoted the growth, angiogenesis and metastasis of BC xenografts. Taken together, this study demonstrated for the first time that circRNA-MYLK might function as competing endogenous RNA (ceRNA) for miR-29a, which could contribute to EMT and the development of BC through activating VEGFA/VEGFR2 and downstream Ras/ERK signaling pathway. Our data suggest that circRNA-MYLK would be a promising target for BC diagnosis and therapy. Graphical abstract: Highlights: circRNA-MYLK level is elevated and correlated with BC progression. circRNA-MYLK plays an oncogenic role in BC in vitro and vivo. circRNA-MYLK directly binds to miR-29a and suppresses miR-29a activity. circRNA-MYLK regulates VEGFA expression by acting as a ceRNA for miR-29a in BC. circRNA-MYLK induces EMT and activates VEGFA/VEGF R2 signaling pathway.